Determination of the Thermal Conductivity Based on a Thermal Capacitor Model. (2015) - Haupt, Sebastian; Lenz, Ernst; Edler, Frank
Abstract: This paper describes a method which enables the calculation of the thermal conductivity κ of thermoelectric materialsduring a simultaneous measurement of the Seebeck coefficient S and the electrical conductivity σ based on a time-resolved measurement of temperature difference across the sample. The described method bases upon the availability of one known external value of κ with low uncertainty. The described method takes advantage of the well-known thermal capacitor model. The simultaneous determination of S, σ and κ enables to calculate the thermoelectric figure of merit ZT = S 2 σT / κ of the specimen in one measurement cycle. This results in lower uncertainties of ZT except when if S, σ and κ are measured separately. The measured values of the thermal conductivity and the resulting thermoelectric figure of merit of metallic samples (ISOTAN ®, steel) and of two semiconducting samples ( Bi -PbTe, FeSi2 ) are presented.